2018
DOI: 10.3390/biomedicines6040114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Yes-Associated Protein (YAP) in Regulating Programmed Death-Ligand 1 (PD-L1) in Thoracic Cancer

Abstract: The programmed death-ligand 1(PD-L1)/PD-1 pathway is an immunological checkpoint in cancer cells. The binding of PD-L1 and PD-1 promotes T-cell tolerance and helps tumor cells escape from host immunity. Immunotherapy targeting the PD-L1/PD-1 axis has been developed as an anti-cancer therapy and used in treating advanced human non-small cell lung cancer (NSCLC) and malignant pleural mesothelioma (MPM). Yes-associated protein (YAP) is a key mediator of the Hippo/YAP signaling pathway, and plays important roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
2
20
0
Order By: Relevance
“…It was recently shown that IL-13 producing cells, type 2 innate lymphoid cells (ILC2s), are destabilized in response to PD-1/PD-L1 pathway upon high-fat feeding resulting in impaired tissue metabolism [20]. Furthermore, PD-1 blockade showed a partial restore in type 2 innate axis and could serve as promising targets of immune-modulatory NASH therapy [21][22][23][24][25]. Importantly, PD-L1 was found to be responsible for HCC development in NASH via inducing the exhaustion of HCC-directed CD8 + T cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that IL-13 producing cells, type 2 innate lymphoid cells (ILC2s), are destabilized in response to PD-1/PD-L1 pathway upon high-fat feeding resulting in impaired tissue metabolism [20]. Furthermore, PD-1 blockade showed a partial restore in type 2 innate axis and could serve as promising targets of immune-modulatory NASH therapy [21][22][23][24][25]. Importantly, PD-L1 was found to be responsible for HCC development in NASH via inducing the exhaustion of HCC-directed CD8 + T cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Yap is a pro-survival signal for cells subjected to various stress environments. For example, Yap modulates the viability of thoracic cancer by affecting the activity of programmed death-ligand 1 (PD-L1) [65]. The inhibition of Yap expression can activate breast cancer cell apoptosis; and in cardiac reperfusion injury, the Yap-Hippo pathway is inhibited and contributes to the progression of cardiac dysfunction by augmenting cardiomyocytes [66].…”
Section: Discussionmentioning
confidence: 99%
“…In the Hippo pathway, YAP is negatively regulated by MST1, MST2, LATS1 and LATS2 kinases through modulated phosphorylation events of kinase cascade in most situations. In addition, YAP activity or function is regulated by many factors that do not influence the LATS/MST kinase activity and have crosstalk with other pathways . CDK7 regulates transcription primarily by phosphorylating serine 5 at the C‐terminal domain of RNA polymerase II, as well as transcription factors such as oestrogen receptor‐α .…”
Section: Discussionmentioning
confidence: 99%